Short stature homeobox 2 methylation as a potential noninvasive biomarker in bronchial aspirates for lung cancer diagnosis - Ni, Shumin (Oncotarget, 2017)
Gene methylation has been frequently observed in lung cancer. However, the use of methylated genes in bronchial aspirates of patients with lung cancer remains to be evaluated. The purpose of this study was to analyze whether the detection of genes with aberrant promoter methylation can be useful noninvasive biomarkers in bronchial aspirates from lung cancer. We found that the methylation status of the cyclin-dependent kinase inhibitor 2A (P16), Ras association domain family 1 isoform (RASSF1A), adenomatous polyposis coli (APC) and short stature homeobox 2 (SHOX2) genes was significantly correlated with lung cancer in bronchial aspirates. The P16, RASSF1A and APC methylation had a bad diagnostic effect in bronchial aspirates of patients with lung cancer compared with non-tumor controls (P16: sensitivity = 0.26, specificity = 0.99, area under the curve (AUC) = 0.67; RASSF1A: sensitivity = 0.40, specificity = 0.99, AUC = 0.66; APC: sensitivity = 0.17, specificity = 0.98, AUC = 0.65). The pooled sensitivity, specificity, and AUC of the SHOX2 methylation were 0.75, 0.94, and 0.94, respectively. Moreover, when squamous cell carcinoma (SCC) was compared to adenocarcinoma (AC), the SHOX2 gene had a significantly higher methylation rate in SCC than in AC (P < 0.001). Methylated P16, RASSF1A, APC and retinoic acid receptor beta2 (RARβ2) genes had similar frequencies in these two histotypes (P > 0.1). Our findings suggest that methylated SHOX2 gene could be a specific and potential noninvasive biomarker using bronchial aspirates for lung cancer diagnosis, especially for SCC.